A Rare Case of Multicentric Liposarcoma and Associated Reproductive Aberrations in a Nonpregnant Holstein-Friesian Crossbred Cow - Pankaj Sood; Parvesh Kumar; Sarvesh Kumar; Adarsh Kumar; Rajesh Kumar Asrani; Madhumeet Singh (Case Reports in Veterinary Medicine)
A five-and-a-half-year-old Holstein-Friesian crossbred cow was repeatedly treated for termination of overgestation, but without any success. On laparotomy, the site indicating fetal-like ballottement on transrectal palpation was occupied by three to four separate caseous and lobulated masses with adhered uterine horns in the omentum. Separation of the utero-omental adhesions retrieved normal-sized uterine horns into pelvic cavity. The right ovary was cystic. Ultrasonography detected another growth in the ventral abdominal musculature. Histopathologically, the omental growths suggested a pleomorphic type of liposarcoma. Presence of omental and muscular liposarcoma along with deep uterine-omental adhesions and a cystic ovary makes this paper a unique addition to the literature.